Low‐Tortuous MXene (TiNbC) Accordion Arrays Enabled Fast Ion Diffusion and Charge Transfer in Dendrite‐Free Lithium Metal Anodes. Issue 30 (28th June 2022) - Cao, Zhenjiang; Chen, Hao; Du, Zhiguo; Gu, Jianan; Zhu, Qi; Li, Bin; Yang, Shubin
Abstract: The widespread implementation of lithium metal anodes is indispensable for reviving high energy density lithium metal batteries. However, the sluggish ion diffusion and high charge‐transfer resistance in metallic lithium anodes hamper their rate capability and practical applications. Here, low tortuous MXene arrays are developed through the ultrafast spreading of an aqueous accordion‐like TiNbC‐MXene dispersion onto a hydrophobic surface. The low tortuous MXene arrays facilitate the fast infiltration of electrolytes, enabling the rapid diffusion of lithium ions. The MXene arrays with Nb species significantly improve the charge transfer in the electrode, homogenizing the electric field. Thus, the low tortuous MXene arrays constructed electrode without lithium dendrites delivers a high‐rate capability (20 mA cm −2 ) with a long cycle life (2500 cycles). Full cells with the dendrite, low tortuosity MXene arrays as anode show a high rate cycle stability up to 1000 cycles (4 C) under conditions of low negative/positive capacity ratio (2.0). Abstract : Thin (15 µm) TiNbC‐MXene accordion arrays with low tortuosity are prepared by a super‐spreading strategy on water/oil interface. Low tortuosity is favorable for electrolyte infiltration, providing fast ion transport; Nb species of MXenes enhance charge transfer, homogenizing the electric field, leading to a high rate capability (20 mA cm −2 ), enabling a practical low‐tortuous lithium anode in high power lithium metal batteries.